STUDY AND IMPLEMENTATION OF ADVANCED ALGORITHMS FOR SPEECH ENHANCEMENT - Zhumabayeva, Dilbar (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This report presents a study of speech enhancement algorithms aimed at reducing ambient noise and improving speech quality. The report focuses on traditional methods such as spectral subtraction as well as advanced methods based on adaptive filters. Implementation of these algorithms was done using MATLAB and evaluation was done using objective measures such as Perceptual Speech Quality Score (PESQ) and Short-Term Objective Intelligibility (STOI). The results indicate the effectiveness of these algorithms in improving speech signals.
Keywords: Speech enhancement; Type of access: Open Access